AN ANALYSIS OF ICT IMPACT ON UKRAINE AND RUSSIA CONFLICT - Debora, Sabaria Catharin (Journal of Social Political Sciences, 2021)
This research discusses the impact of information and communication technology (ICT) on the conflict between Ukraine and Russia that led to the annexation of Crimea by Russia in 2014. This study uses qualitative approach to analyze the selected issue. The data were taken from case study articles and official websites. The analysis of the formulated problem is carried out by combining hegemony theory, agenda setting theory and securitization theory. The agenda setting theory of Maxwell E. McCombs and Donald L. Shaw is used to analyze the use of ICT, Antonio Gramsci’s hegemony theory is used to analyze the hegemony of ICT in Ukraine and Russia, while Barry Buzan’s theory of securitization is used to analyze the negative effects of the abuse of ICT during the duration of the conflict. The research found that ICT has significant impact and influence in Ukraine and Russia conflict and is a clear example of the use of ICT abuse in Eastern Europe. The information war between Russia and Ukraine led to the annexation of Crimea by Russia. The success of Russia in annexing Crimea without armed contact and casualties is a clear evidence of how ICT can be an effective and efficient weapon to achieve national interests. From the analysis, it can be concluded that the development of ICT not only bring a positive impact on the society, but also negatively affect modern conflict, such as seen in the conflict between Ukraine and Russia.